Mitigation efforts will not fully alleviate the increase in water scarcity occurrence probability in wheat-producing areas - Trnka, Miroslav; Feng, Song; Semenov, Mikhail A; Olesen, Jørgen E; Kersebaum, Kurt Christian; Rötter, Reimund P; Semerádová, Daniela; Klem, Karel; Huang, Wei; Ruiz-Ramos, Margarita; Hlavinka, Petr; Meitner, Jan; et al. (Science advances, 2019)
Global warming is expected to increase the frequency and intensity of severe water scarcity (SWS) events, which negatively affect rain-fed crops such as wheat, a key source of calories and protein for humans. Here, we develop a method to simultaneously quantify SWS over the world's entire wheat-growing area and calculate the probabilities of multiple/sequential SWS events for baseline and future climates. Our projections show that, without climate change mitigation (representative concentration pathway 8.5), up to 60% of the current wheat-growing area will face simultaneous SWS events by the end of this century, compared to 15% today. Climate change stabilization in line with the Paris Agreement would substantially reduce the negative effects, but they would still double between 2041 and 2070 compared to current conditions. Future assessments of production shocks in food security should explicitly include the risk of severe, prolonged, and near-simultaneous droughts across key world wheat-producing areas.
Keywords: Seasons; Triticum; voda; klimatické změny; Humans; lidé; globální oteplování; Crops, Agricultural; teoretické modely; Models, Theoretical; zemědělské plodiny; roční období; Geography; pšenice; zásobování potravinami; Global Warming; Food Supply; Water; zeměpis; Climate Change